2009
DOI: 10.1534/genetics.108.096453
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Consequences of Background Effects onscallopedMutant Expressivity in the Wing ofDrosophila melanogaster

Abstract: Genetic background effects contribute to the phenotypic consequences of mutations and are pervasive across all domains of life that have been examined, yet little is known about how they modify genetic systems. In part this is due to the lack of tractable model systems that have been explicitly developed to study the genetic and evolutionary consequences of background effects. In this study we demonstrate that phenotypic expressivity of the scalloped E3 (sd E3 ) mutation of Drosophila melanogaster is backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 69 publications
(74 reference statements)
2
71
1
Order By: Relevance
“…There is substantial evidence that wild-type genetic background almost always modulates the phenotypic effects of mutations (e.g., McKenzie et al 1982;Threadgill et al 1995;Atallah et al 2004;Milloz et al 2008;Chandler 2010;Dowell et al 2010;Gerke et al 2010). The influence of wild-type genetic backgrounds also extends to interactions among mutations (Remold and Lenski 2004;Dworkin et al 2009;Wang et al 2013b), altering patterns of epistasis, and these complex interactions are likely widespread . Alleles that influence many mutant phenotypes segregate in most natural populations, representing a potential source of cryptic genetic variation Félix 2007;Vaistij et al 2013).…”
mentioning
confidence: 99%
“…There is substantial evidence that wild-type genetic background almost always modulates the phenotypic effects of mutations (e.g., McKenzie et al 1982;Threadgill et al 1995;Atallah et al 2004;Milloz et al 2008;Chandler 2010;Dowell et al 2010;Gerke et al 2010). The influence of wild-type genetic backgrounds also extends to interactions among mutations (Remold and Lenski 2004;Dworkin et al 2009;Wang et al 2013b), altering patterns of epistasis, and these complex interactions are likely widespread . Alleles that influence many mutant phenotypes segregate in most natural populations, representing a potential source of cryptic genetic variation Félix 2007;Vaistij et al 2013).…”
mentioning
confidence: 99%
“…In addition we included genes that appear to be expressed in the developing wing imaginal discs and in particular show evidence of differential expression on the basis of previous studies. (Klebes et al 2002(Klebes et al , 2005Butler et al 2003;Li and White 2003;Dworkin et al 2009). See supporting information, Table S1 for a list of genes included on this array, as well as probe sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Any arrays that demonstrated obvious signs of poor hybridization were excluded. Conservatively we used 216 of the arrays for analysis, of which 16 were for the replication of the study of Dworkin et al (2009), to assess the general performance of the custom array platform. Thus 200 arrays were used for analyses described in this study, leading to an unbalanced design.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that genetic background effects contribute to the phenotypic consequence of a mutation, even if little is known about how these effects modify genetic systems. In the Drosophila model system, Dworkin et al [36], working on the background effect on the expressivity of a Scallopped mutation, found that the phenotype is mediated through the misregulation of a series of developmental patterning genes, the epistatic interaction between mutated genes is background dependent, and the phenotypic variations correlate with qualitative and quantitative differences in downstream gene expression.…”
Section: The Genetic Background Effectmentioning
confidence: 99%